Human-Animal Relationship: How Does it Affect Animal Performance and Welfare? (Indian Journal of Animal Production and Management, 2024)
In modern intensive farming systems,  animals are always subjected to some degree of  human contact. The quality of human-animal  interactions has a profound impact on the  productivity and welfare of farm animals. Regular  pleasant contact with humans may result in  desirable alterations in the physiology, behaviour,  health and productivity of farm animals. In contrast,  animals subjected to aversive human contact may  become highly fearful of humans and their growth  and reproductive performance will be  compromised. An animal’s perception of humans in  the presence of humans, results in frightening,  neutral and pleasant emotions. A regular positive  human contact or handling is a powerful and reliable  method to reduce the stress and fear reactions in  farm animals whereas negative handling by  stockperson is negatively correlated with milk yield,  protein and fat content. Human contact may cause  alterations in brain physiology and morphology as  the farm animals encountering challenging  conditions often show some degree of  immunosuppression. This paper discusses the  importance of good human-animal relationship for  improving animal welfare and production with  special reference to dairy animals.
Keywords: human-animal relationship; animal performance; animal welfare; animal productivity